The relationship between the umbilical cord length and it's diameter with the total CD34+ and total nucleated cell (TNC) as a parameter of cord blood selection - Meiliza Indriani; Ya’kub Rahadiyanto; Yusuf Effendi; Bayu Winata Putera; Zen Hafy (Acta Biochimica Indonesiana, 2018)
Background: The stem cell transplantation successful influenced by the quality of the umbilical cord blood which includes the number of CD34 + and Total Nucleated Cells (TNC). Objectives: The study aims to determine the correlation between umbilical cord length and it’s diameter, with the number of CD34 + and TNC cells as indicators of the quality of cord blood storage feasibility. Several other factors as maternal age, gestation period, and infant birth weight also examined. Methods: Thirty four of umbilical cords from the delivered woman in Dr. Mohammad Hoesin Hospital (RSMH) Palembang were collected from May to June 2018. The length and diameter of the cord were immediately measured after delivery. The evaluated cells were counted with a flow cytometer at Klaster Stem Cell and Tissue Engineering Research Centre (SCTE) IMERI Faculty of Medicine University of Indonesia (FKUI). Results: Spearman correlation test show that there was no correlation between the length and diameter of the umbilical cord, maternal age, gestational period and infant weight, with the number of CD34 + and TNC cells in the cord (p> 0.05). However, the profile analysis indicated that the longer and larger the diameter of the umbilical cord, the higher concentration of the CD34+ and TNC cells. Conclusion: This study suggested that the younger maternal age, older gestational age, and higher infant birth weight, also normal hemoglobin level, tend to increase the number of CD34+ and TNC cells in the cord blood.